Pengaruh Perubahan Organisasi, Budaya Organisasi Dan Perilaku Kerja Terhadap Kinerja Karyawan Di PT Sisirau Medan - Sunaryo Sunaryo (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
The purpose of this study is to determine the effect of the organizational change, organizational culture and work behavior on performance, The population of this study are all employees and leaders who work in PT Sisirau Medan that is as much as 80 respondents. The sample used in this study is a saturated sample, using the entire population as a sample of 80 people. Data were collected using observations and questionnaires. Furthermore, data analysis is tested by using multiple regression analysis, t test, F test and coefficient of determination. The result of this research is organizational change has a significant effect on employee performance, the influence of organizational change on employee performance is 95.6%. Organizational Culture has a significant effect on employee performance, the amount of influence of Organization Culture on employee performance is 71.2%. Work Behavior has a significant effect on employee performance, the effect of Work Behavior on employee performance is 31.2%. Simultaneously Organizational Change, Organizational Culture, and Work Behavior have a significant effect on Employee Performance in PT Sisirau Medan. The amount of Organizational Change, Organizational Culture, and Work Behavior in explaining performance is 79.9% while the remaining 20.1% is explained by other variables not included in this research model.